THE EQUIVALENCE OF THE INDONESIAN TRANSLATION OF CHRISTIANITY-RELATED TERMS IN DAN BROWN’S ANGELS AND DEMONS - Harris Hermasnyah Setiajid; Almira Ghassani Shabrina Romala; Theresia Enny Anggraini; Angela Marici Yuca Amadea (Universitas Bandar Lampung, 2021)
Different literary works are translated. Angels and Demons by Dan Brown. Even if the message changes during the communication process, the translation must maintain the original meaning. To create appropriate connection between the author and the reader, the translated Christian terminology in Angels and Demons must be equivalent to the original. This study's major goal is to categorize the equivalency and readability of Christian terminology in the novel. They are interpreted in various ways, and some phenomena occur during conversion. Because the translator's understanding is different from the readers', the researcher attempts to compare the translation. The readability of the terms can be answered by the equivalency of the translation. This study used library and survey methodologies. Using the library technique, researchers compared many theories and studies. The researcher gave out questionnaires with Christian words translated into Indonesian. Christian and non-Christian responses were separated. The researcher used the data from the respondents to obtain the solutions to this study problem formulation, which is the equivalency and legibility of Christian-related phrases. The chosen data have some special differences in the TL products based on the categorization of the data. In terms of TL's product, both dynamic and formal translation have different processes in selecting diction for the TL's reader. Because no other diction truly represents the meaning of the chosen diction, the official translation manages to be stiff and conventional. The categorizations dynamic translation is flexible and offers numerous options.